(untitled) (SMC Journal Shadananda Multiple Campus, 2025)
This article investigates the chronic issue of late school attendance among secondarylevel students. It examines the causes, effects, and potential solutions to this issue, with a particular focus on students within the Shadananda Municipality. The study employed a mixed-method approach, combining surveys, interviews, and academic record analysis to provide a comprehensive overview. Results indicated that factors such as personal issues, transportation difficulties, school-related issues, and health problems contribute to late attendance. The impact of tardiness includes academic under performance, classroom disruption, behavioral problems, and social isolation. The article concludes by recommending strategies for improvement, including parental involvement, improved transportation solutions, incentives for punctuality, clear school policies, and health and well-being programs. Attending school on time is beneficial for the personality development of students, and the school also attracts honest and disciplined students. This report provides a comprehensive overview of the issue of late school attendance, serving as a basis for further discussions on how to promote better punctuality among secondary school students. It is a chronic problem for secondary-level students who arrive late each day. This study examined the factors contributing to the late attendance of the Shadananda Municipality. When students are late to class, they often forget to sing the national anthem. They are unknown to teachers, and they are also deprived of the teacher’s love and affection. They also get punishment from teachers. Therefore, I chose this topic for my research article to address this problem.